“The whistle blows, and we are whisked into a tunnel”: Railways and the Environment in Illawarra, 1850s–1915 - Brett, Andre (2021)
Historians are becoming alert to the large role of railways in environmental history. To date, many studies in Australasia focus on a specific industry, such as timber. It is now worth turning to the distinctive local or regional effects of railways beyond a single industry or commodity, so to better understand the links between technology, environment, and place. Illawarra presents a valuable case study. The environmental history of the first decades of rail transport exposes how Wollongong and its region industrialised and the ways in which this process affected everything from primary producers to the sounds of daily life. This article takes in the 1850s through to the start of World War I (WWI), a period when rail transport grew from being the adjunct of a few coal mines into an essential common carrier. It progresses through a series of themes that show the economic, social, and cultural attributes that shaped and were shaped by the railway environment. It begins with the railway as a carrier: the extent to which trains fulfilled their intended role to transport Illawarra’s natural resources to Sydney and other markets. It then moves on to the railway as a consumer, putting the local environment to work for its benefit and requiring materials made from resources of distant lands. Railways did more than carry or consume resources; they created their own environment and provided new perspectives on nature. Trains brought people closer to nature, carried them into new—and dangerous—environments in tunnels, and transformed the sonic landscape. Rail travel differed significantly to horseback or sea voyages in capacity and speed, and by WWI it was enmeshed in Illawarra’s environment.